Child's Personality and Family Upbringing Methods - AL-Momani, Mohammad Omar (Indonesian Journal of Instructional Media and Model, 2022)
Psychologists point out that there are critical and highly sensitive periods in the development of children during which learning of their behavior patterns becomes possible, that is, there are certain environmental interactions during this period in order to progress naturally, and at the beginning of his interaction he can issue a greater number of responses with his environment , but whatever What remains of it and proves is what keeps it consolidating, and what fades and is deleted from the responses, it is the one that does not support, and the child in the characteristics of his first life suffers from what befalls others and suffers from psychological disorders and emotional and behavioral deviations as adults suffer. The psychological, emotional and physical development of the child is a continuous and escalating process, which is In its growth and gradation, it is affected by the factors of the physical environment and the social family